Case Report: Auditory Neuropathy and Central Auditory Processing Deficits in a Neuro-Otological Case-Study of Infratentorial Superficial Siderosis - Kharytaniuk, Natallia; Cowley, Peter; Werring, David J.; Bamiou, Doris-Eva (Frontiers in Neurology, 2021)
Hearing and balance impairment are the most frequently reported features of infratentorial (classical) superficial siderosis (iSS). There are few comprehensive descriptions of audiovestibular function in iSS and therefore limited understanding of the affected segment(s) of the audiovestibular pathway. In addition, monitoring disease progression and response to treatment is challenging and currently mainly guided by subjective patient reports and magnetic resonance imaging. To the best of our knowledge, there have been no previous reports assessing central auditory function in iSS. We describe such findings in a patient with iSS in an attempt to precisely localise the site of the audiovestibular dysfunction, determine its severity and functional impact. We confirm the presence of (asymmetrical) auditory neuropathy and identify central auditory processing deficits, suggesting involvement of the central auditory pathway beyond the brainstem. We correlate the audiological and vestibular findings with self-report measures and the siderosis appearances on brain magnetic resonance images.